Transcutaneous bilirubin in newborns before, during, and after home phototherapy-Results from a secondary analysis of a randomized controlled trial. - Felicia Erlandsson Speychal; Miriam Pettersson; Mats Eriksson; Andreas Odlind; Andreas Ohlin (PLoS ONE)
Home phototherapy is recommended as an alternative to hospital-based therapy for neonatal jaundice in otherwise healthy full-term infants. With a reliable device for transcutaneous bilirubin (TcB) measurement, bilirubin values could be monitored at home during treatment. This study aimed to examine the accuracy of TcB measurement of bilirubin levels before, during, and after home phototherapy. Patients requiring phototherapy were assigned to home (intervention) or hospital-based phototherapy (control). Transcutaneous bilirubin measurement was made at the sternum (uncovered skin) and at sacrum (covered by the diaper during treatment). Simultaneously, total serum bilirubin (TSB) level was collected through a blood sample. The agreement between TcB and TSB before, during, and after phototherapy was assessed using Bland-Altman plots. Altogether 141 patients and 856 paired bilirubin values were included. The results show that TcB measurements underestimate TSB levels. Before phototherapy, the mean difference between TcB and TSB was 75 ± 36 μmol/L at the sternum and 135 ± 39 μmol/L at sacrum, with no difference between study groups. During phototherapy, the mean difference at the sternum was larger in the control group, 105 ± 73 μmol/L, than in the intervention group, 50 ± 41 μmol/L; at sacrum, the mean difference was 125 ± 44 μmol/L, comparable in both study groups. After phototherapy, the TcB-TSB agreement improved, with a mean difference of 29 ± 33 μmol/L (sternum) and 87 ± 35 μmol/L (sacrum), and no difference between study groups. In conclusion this study shows that full-term infants who qualified for phototherapy show poor agreement between TcB measurement and TSB, suggesting that TcB measurements cannot replace measurement of TSB level before, during, or after home phototherapy.